Development Of Mobile-Based Attendance Management System Applications - Alexander Achmad Khan; Diki Gita Purnama; Arya Maulana Kurniawan (Publikasi Indonesia, 2023)
Components in evaluating student academic achievement can be seen from several things, including attendance. Recording attendance or absenteeism in courses is one of the factors for assessing academic performance and student activities in the learning process. Errors in recording attendance are human errors that can be detrimental to students. This research aims to develop a mobile-based application with the Android platform to overcome errors in attendance. Application software development uses the Agile method; the research results are applications that can overcome human error problems, and development using the Agile method can be done more quickly